2021
DOI: 10.1101/2020.12.27.20248903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term neurological manifestations of COVID-19: prevalence and predictive factors

Abstract: BackgroundPreclinical and clinical investigations have argued for nervous system involvement in SARS-CoV-2 infection and for long term sequalae including neurological manifestationsMethodsa sample of 208 previously hospitalized COVID-19 patients, 165 patients were re-assessed at 6 months according to a structured standardized clinical protocol. Premorbid comorbidities and clinical status, severity of COVID-19 disease, complications during and after hospitalization were recorded.ResultsAt 6-month follow-up afte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 22 publications
1
30
0
4
Order By: Relevance
“…Finally, other studies evaluating heterogenous populations of mild-to-severe COVID-19 patients further confirmed persistent loss of smell up to 6 months after symptom onset (57,61,62,64,121,122). Moein et al in a prospective study on 82 mild-to-severe COVID-19 patients showed smell loss in ∼37% of patients at 2 months of follow-up (57).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 78%
See 4 more Smart Citations
“…Finally, other studies evaluating heterogenous populations of mild-to-severe COVID-19 patients further confirmed persistent loss of smell up to 6 months after symptom onset (57,61,62,64,121,122). Moein et al in a prospective study on 82 mild-to-severe COVID-19 patients showed smell loss in ∼37% of patients at 2 months of follow-up (57).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 78%
“…At the same follow-up, a prospective study on 138 patients and a retrospective study on 90 mild-tosevere patients showed persistent hyposmia in 5-8% of patients (57,67). Lastly, Pilotto et al, by examining retrospectively 165 patients detected the presence of hyposmia in ∼15% of patients at up to 6 months of follow-up (61).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 92%
See 3 more Smart Citations